(untitled) (Research, Society and Development, 2024)
The increasing resistance of microorganisms against antibiotics puts at risk the human being. This event requires urgently developing strategies for producing alternative antibacterial agents. The combination of green silver nanoparticles (reduced by essential oil) and molybdenum disulfide can be synergistically explored given the interaction of components. Herein, it is reported the response of isolated and combined components with resulting outstanding kinetics of kill-time (complete elimination of Staphylococcus aureus and Escherichia coli after four hours of contact), effective action against biofilm formation ( 99% of inhibition in the biofilm formation). These results confirm that the intercalation of silver nanoparticles between exfoliated sheets of MoS2 represents a promising strategy to develop efficient antibacterial agents against Gram-positive and Gram-negative bacteria.